A Survey of Student Satisfaction At The University of Malaya Library - Zaiton, O.; Kaur, Kiran; Zanaria, Saupi Udin (University of Malaya Library, 2003)
A user survey was undertaken on 28 February 2003 to obtain feedback from students in 3 areas: collection, services and facilities. The objectives of the survey were to investigate whether students use the library collection and for what purpose, whether students are aware of and use the services offered by the library, and whether students are aware of the user education programme offered by the library. The final sample comprised 1,315 students randomly selected from various libraries within the network and residential colleges in the campus. Seven hundred and fifty one questionnaires representing 57.11 percent were completed and returned. Findings show that a majority of the users visit the library at least once a month. The print collection of the library is still most popularly used by student, both postgraduates and undergraduates. The most prominent problem faced by students is insufficient copies of books to be borrowed. The postgraduates report that they use library materials mostly to prepare their assignments and a majority of the undergraduates use the library to study for exams. As expected the postgraduates reported a higher usage of online databases. Students have also recorded satisfaction with the various services provided by the library. With regard to the user education programmes at the library, students have recorded a high awareness of the service but they do find the programme difficult to understand. This survey gives the library much leverage to prepare its collection and services to meet the needs of its students.